Big game - Millar, Mark (Image Comics, Inc., 2023)
Wesley Gibson is back, and he rules the world from the shadows. Can the combined forces of Kick-Ass, Hit-Girl, Kingsman, The Magic Order, Huck, Night Club, and the Ambassadors stop him?